Potential Interplay between Dietary Saturated Fats and Genetic Variants of the NLRP3 Inflammasome to Modulate Insulin Resistance and Diabetes Risk: Insights from a Meta‐Analysis of 19 005 Individuals. Issue 22 (12th September 2019) - Murphy, Aoife M.; Smith, Caren E.; Murphy, Leanne M.; Follis, Jack L.; Tanaka, Toshiko; Richardson, Kris; Noordam, Raymond; Lemaitre, Rozenn N.; Kähönen, Mika; Dupuis, Josée; Voortman, Trudy; Marouli, Eirini; et al.
Abstract : Scope: Insulin resistance (IR) and inflammation are hallmarks of type 2 diabetes (T2D). The nod‐like receptor pyrin domain containing‐3 (NLRP3) inflammasome is a metabolic sensor activated by saturated fatty acids (SFA) initiating IL‐1β inflammation and IR. Interactions between SFA intake and NLRP3‐related genetic variants may alter T2D risk factors. Methods: Meta‐analyses of six Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium ( n = 19 005) tested interactions between SFA and NLRP3‐related single‐nucleotide polymorphisms (SNPs) and modulation of fasting insulin, fasting glucose, and homeostasis model assessment of insulin resistance. Results: SFA interacted with rs12143966, wherein each 1% increase in SFA intake increased insulin by 0.0063 IU mL −1 (SE ± 0.002, p = 0.001) per each major (G) allele copy. rs4925663, interacted with SFA (β ± SE = −0.0058 ± 0.002, p = 0.004) to increase insulin by 0.0058 IU mL −1, per additional copy of the major (C) allele. Both associations are close to the significance threshold ( p < 0.0001). rs4925663 causes a missense mutation affecting NLRP3 expression. Conclusion: Two NLRP3‐related SNPs showed potential interaction with SFA to modulate fasting insulin. Greater dietary SFA intake accentuates T2D risk, which, subject to functional validation, may be further elaborated depending on NLRP3‐related genetic variants. Abstract : The NLRP3 inflammasome is a metabolic sensor activated by saturated fatty acids initiating IL‐1β inflammation and insulin resistance. A genome‐wide candidate meta‐analysis of NLRP3 genetic variants in 19 005 participants highlights two NLRP3 single‐nucleotide polymorphisms that interact with dietary saturated fat to increase insulin concentrations. Identifying inflammatory gene–nutrient interactions may facilitate identification of individuals at high type 2 diabetes risk.